(untitled) (Global Media Journal - German Edition, 2024)
This debate was part of the conference “Internationalizing German Communication Studies: Learning from the World” in Erfurt, Germany, in March 2024. It featured an in-depth dialogue with scholars from South Africa, Brazil and Qatar about approaches to internationalization in their respective academic communities. The aim was to learn about the current state of internationalization in communication studies around the world, particularly in places often termed the “Global South”, and to understand their discourses, respective challenges, and opportunities for internationalization. The comparative perspective applied here allows for a deeper understanding of power asymmetries, language and translation issues, and the pros and cons of intellectual autonomy. It also addresses how to overcome “islandization” on the path to a true and just, or a “deep” internationalization in communication studies.